Transformation Of The Youth Of New Uzbekistan In Social And Innovative Processes: A Sociological Analysis (Eurasian Journal of Humanities and Social Sciences, 2023)
This article analyzes the role of youth in the sustainable development of the social structure. The existing scientific concepts were given and analyzed the work of young people to develop our society. The author thought about how youth's role in the sustainable development of the social structure is played. Simultaneously, the article revealed reforms, the necessary measures carrying out in Uzbekistan for the formation of young people as an active group of our society.